HUBUNGAN PEMAHAMAN TENTANG IDEOLOGI PANCASILA DENGAN SIKAP NASIONALISME (STUDI PADA ANGGOTA BIDANG KEPEMUDAAN DAN OLAHRAGA SERTA BIDANG PENDIDIKAN DAN KESENIAN DI PERKUMPULAN MASYARAKAT SURAKARTA) - Saputro, Yulianto Dwi; ., Triyanto; ., Wijianto (PKn Progresif, 2016)
The objective of this research is to investigate whether or not there is a correlation between the variable of the understanding of Pancasila (Indonesian Philosophy) Ideology and that of the Nationalism Attitude (A Study on the member of Youths, Sports, and Education & Art Field of Surakarta Community Association).The result of research shows that there is a correlation between the understanding of Pancasila (Indonesian Philosophy) Ideology and the Nationalism Attitude (A Study on the member of Youths, Sports, and Education & Art Field of Surakarta Community Association) as indicated by the result of the analysis in which the value of rxy was 0.416. It was consulted to the value of rtable with N=79 at the significance level = 0.05, which resulted in the value of rtable = 0.220. Because the value of rtable= 0.416 was greater than 0.220, Ha was verified, but Ho was not verified. Thus, there is there is a correlation between the understanding of Pancasila (Indonesian Philosophy) Ideology and the Nationalism Attitude. The result of the correlation coefficient significance based on the t test shows that the value of tcount was 4.010. The result was consulted to the value of ttable = 1.991at the significance level of 5%. Because the value of tcount = 4.010 was greater than that of ttable= 1.991, the correlation coefficient was significant, meaning that H0 was not verified, but Ha was verified. Thus, there was a correlation between the understanding of Pancasila (Indonesian Philosophy) Ideology and the Nationalism Attitude.